In situ observation of crystal reorientation in polygranular graphite by synchrotron X-ray diffraction and neutron imaging - Zillhardt, T; Burca, G; Ludwig, W; Liu, D; Marrow, TJ (Elsevier, 2023)
The capacity of polygranular graphite to accommodate strain is important to its use within structural components. This study has used in situ neutron and synchrotron X-ray experiments to demonstrate that reorientation of crystal domains accompanies the accommodation of applied mechanical strain in unirradiated Gilsocarbon (GCMB/IM24) graphite. Orientation changes were observed using 3D X-ray Diffraction, and local changes in neutron scattering were also observed with energy-resolved Bragg-edge neutron imaging. In both cases, this behaviour at the crystal level was partially recovered when the load was removed. This study provides new evidence for crystal deformation mechanisms that contribute to polycrystalline graphite's elastic non-linearity and the development of permanent set, which may also explain the effects of fast neutron irradiation on graphite elastic behaviour.